2008
DOI: 10.1016/j.brainres.2008.01.045
|View full text |Cite
|
Sign up to set email alerts
|

Caspase activation in fetal rat brain following experimental intrauterine inflammation

Abstract: Intrauterine inflammation has been implicated in developmental brain injuries, including the development of periventricular leukomalacia (PVL) and cerebral palsy (CP). Previous studies in our rat model of intrauterine inflammation demonstrated apoptotic cell death in fetal brains within the first 5 days after lipopolysaccharide (LPS) administration to mothers and eventual dysmyelination. Cysteine-containing, aspartate-specific proteases, or caspases, are proteins involved with apoptosis through both intracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…We recently found that neuronal cell death differs within hours of birth in mice born into a germ-free vs. a conventional environment (43). Similarly, perinatal rats show increased expression of cell death genes in the brain at 2-8 h after exposure to lipopolysaccharide, a component of bacterial cell walls (44,45). Microbial invasion at birth is associated with the release of inflammatory cytokines (17), and vaginally-born and C-section-born subjects have differing blood cytokine levels (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…We recently found that neuronal cell death differs within hours of birth in mice born into a germ-free vs. a conventional environment (43). Similarly, perinatal rats show increased expression of cell death genes in the brain at 2-8 h after exposure to lipopolysaccharide, a component of bacterial cell walls (44,45). Microbial invasion at birth is associated with the release of inflammatory cytokines (17), and vaginally-born and C-section-born subjects have differing blood cytokine levels (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…A strong case can be made for a role of the microbiome. Castillo-Ruiz et al (1) previously reported that altering the microbiomial environment increases cell death in the PVN a few hours after birth [i.e., in germ-free mice (6)], and others have found differences in cell death-related genes in response to altering the bacterial environment of neonates (7,8). Furthermore, the microbiome is associated with the immune system, including cytokines that can cross into the CNS via the blood-brain barrier.…”
Section: Searching For a Mechanismmentioning
confidence: 99%
“…When it comes to bacterial infection, LPS exposure was reported to induce microglia to increase the secretion of TNF- α that increased neuron apoptosis via the caspase-3 pathway in the developing cerebral cortex [ 12 ]. In addition to increased apoptosis, LPS exposure was found to lead to decreased neurogenesis in the brain after [ 13 , 14 ]. Therefore, bacterial meningitis may cause apoptosis of a neuron cell and decease neurogenesis though the NF- κ B and TNF- α pathways.…”
Section: Introductionmentioning
confidence: 99%